2013
DOI: 10.1177/0266666913497611
|View full text |Cite
|
Sign up to set email alerts
|

Records surveys in support of a framework for managing public records in Zimbabwe

Abstract: The purpose of this study is to demonstrate that records surveys are a critical function that supports a framework for managing public records. The study was motivated by the recognition that the key step in ensuring that records are properly managed on a continuing basis at each stage of the life cycle is to examine all records created and maintained by an office through, among other activities, conducting a records and information management survey. The study employed a quantitative methodology to gather dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
1
13
0
3
Order By: Relevance
“…Instead, they see them as witch hunts and fault-finding exercises. This has also been observed by Chaterera (2008; 2013) in the Midlands Province and by Maboreke (2007) in Masvingo Province of Zimbabwe. Thus, at the end of the day, some public officers do not fully benefit from records surveys due to the negative ideas that they hold.…”
Section: Data Analysis and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Instead, they see them as witch hunts and fault-finding exercises. This has also been observed by Chaterera (2008; 2013) in the Midlands Province and by Maboreke (2007) in Masvingo Province of Zimbabwe. Thus, at the end of the day, some public officers do not fully benefit from records surveys due to the negative ideas that they hold.…”
Section: Data Analysis and Discussionsupporting
confidence: 55%
“…Documentary evidence has indicated that there are poor records management practices in many of these public departments (Garaba 2000; Kaimbanemoyo 1996; Tsvuura 2003). Chaterera (2008) has noted poor records maintenance in the Midlands Province and so has Maboreke (2007) in Masvingo Province, despite the fact that the National Archives of Zimbabwe holds periodic records management surveys in these departments and in these provinces. Mutare (2009) and Tsaura (2011) expressed dismay at the manner in which public records were maintained at Chitungwiza Hospital and Midlands Provincial Education Office respectively.…”
Section: Records Maintenancementioning
confidence: 99%
“…">PendahuluanPelaksanaan survei arsip dinamis di suatu organisasi dapat mempengaruhi berbagai kegiatan, terutama dalam kegiatan pengembangan manajemen arsip dinamis. Chaterera menyatakan bahwa survei arsip dinamis adalah latihan kritis yang dilakukan untuk mencapai pelaksanaan pengelolaan arsip dinamis yang tepat dan sesuai dalam departemen publik (Chaterera, 2013). Berdasarkan pernyataan dalam Misi National Archive of Zimbabwe tahun 2015, pusat arsip melakukan pemeriksaan terhadap penciptaan, penggunaan, pemeliharaan dan penyusutan arsip dinamis serta memberikan nasihat mengenai penyimpanan Ratu Nabilah Nur'aini dan Margareta Aulia Rachman…”
unclassified
“…Penyusunan arsip seperti ini menyulitkan ketika suatu saat arsip dinamis dibutuhkan kembali. Survei arsip dinamis merupakan tahapan yang utama untuk mendukung kegiatan manajemen arsip dinamis(Chaterera, 2013). Kegiatan manajemen arsip dinamis dilakukan untuk memudahkan dalam temu kembali arsip yang dibutuhkan oleh pengguna.…”
unclassified
See 1 more Smart Citation